ETHNIC DIFFERENCES IN SEDENTARY BEHAVIOR AND CARDIOMETABOLIC RISK BIOMARKERS IN POSTMENOPAUSAL WOMEN. (16th November 2018) - Bellettiere, J; Ervin, D; Godbole, S; Keshavarz, S; Maestas, J; Chang, Y; Sears, D
Abstract: This project assessed ethnic differences in objectively-measured sedentary behavior and cardiometabolic risk biomarkers among overweight/obese postmenopausal women (n=518; mean age 63 ± 6 years). Data from hip-worn accelerometers were processed using validated machine-learning algorithms to measure total daily sitting time and mean sitting bout duration (an indicator of sedentary behavior patterns), both of which are associated with cardiometabolic disease risk. Hispanic women (n=102) differed significantly from non-Hispanic women (n=416) having less total sitting time (41 minutes less/day, p=0.00012) and shorter mean sitting bout duration (3 minutes less, p=0.049). After adjusting log-linear regression models for socio-demographic and other confounding factors including moderate-to-vigorous physical activity, Hispanic women, compared to non-Hispanic women, had significantly greater fasting glucose, insulin, and insulin resistance (HOMA-IR; p<0.05 | all); lower total cholesterol and HDL (p<0.05 | all); and LDL, body mass index (BMI), and waist circumference (WC) were not significantly different. Among all women, greater total sitting time was deleteriously associated with insulin, HOMA-IR, triglycerides, BMI and WC, while longer sitting bout durations were deleteriously associated with glucose, insulin, HOMA-IR, and WC (p<0.05 | all). The association between longer bout duration and fasting glucose was significantly greater among Hispanic than non-Hispanic women (p-interaction=0.034). This study demonstrates deleterious associations between two objectively-measured parameters of sitting behavior and cardiometabolic disease-risk biomarkers in overweight/obese older women. These results highlight ethnic differences in sitting behaviors and suggest that associations of sedentary behavior patterns and glucose vary by ethnicity, with more deleterious associations observed for Hispanic women. Corroboration in larger cohort studies is warranted.